Metabolisable energy partition for Japanese quails - Silva, E. P. [UNESP]; Castiblanco, D. M. C. [UNESP]; Artoni, S. M. B. [UNESP]; Lima, M. B. [UNESP]; Nogueira, H. S. [UNESP]; Sakomura, N. K. [UNESP] (Cambridge Univ Press, 2020)
Knowing how energy intake is partitioned between maintenance, growth and egg production (EP) of birds makes it possible to structure models and recommend energy intakes based on differences in the BW, weight gain (WG) and EP on commercial quail farms. This research was a dose-response study to re-evaluate the energy partition for Japanese quails in the EP phase, based on the dilution technique to modify the retained energy (RE) of the birds. A total of 300 VICAMI(R)Japanese quail, housed in climatic chambers, were used from 16 weeks of age, with averages for BW of 185 g and EP of 78%, for 10 weeks. To modify the RE in the bird's body, a qualitative dilution of dietary energy was used. Ten treatments (metabolisable energy levels) were distributed in completely randomised units, with six replicates of five quails per experimental unit. Metabolisable energy intake (MEI), egg mass (EM) and RE were expressed in kJ/kg(0.67). The utilisation efficiency (k(t)) was estimated from the relationship between RE and MEI. The metabolisable energy for maintenance was given by RE = 0. The net energy requirement for WG was obtained from the relationship between RE in the BW as a function of the BW. The utilisation efficiency for EP (k(o)) was obtained from the relationship between EM and RE corrected MEI for maintenance and WG. Based on these efficiencies, the requirements for WG and EM were calculated. The energy intake by Japanese quails was partitioned according to the model: MEI = 569.8 x BW0.67+ 22 x WG + 13 x EM. The current study provides procedures and methods designed for quails as well as a simple and flexible model that can be quickly adopted by technicians and poultry companies.
Keywords: egg production; egg weight; evaluation of models; retained energy; maintenance